The use of diversified and dialogic strategies in teaching about the Arthropoda phylum: experience report of the contributions of supervised internship (Research, Society and Development, 2021)
This work consists of an experience report developed during the Supervised Internship discipline of a Licentiate Degree in Biological Sciences. Describes and reflects on the experience of conducting, developing and applying diversified and dialogical strategies and didactic instruments in teaching about anatomy, morphology and ecological importance of the Arthropoda phylum. The didactic methodology was developed in four phases: Initial problematization; Development of the teaching narrative; Applying knowledge; and finally, Reflecting on what was learned. With the use of diversified and dialogic strategies, positive results were observed in the students' learning, not only regarding conceptual content, but also procedural and attitudinal important for critical training and awareness of environmental preservation. In addition to assisting in the motivation and active participation of students. It is concluded that the praxis promoted by the activities developed during the Supervised Internship was fundamental for the consolidation of the knowledge built during graduation, being a fundamental step for the formation and future teaching performance.